An Investigation into the Relation between the Technique of Movement and Overload in Step Aerobics - Rutkowska-Kucharska, Alicja (Appl Bionics Biomech, 2017)
The aim of this research was to determine the features of a step workout technique which may be related to motor system overloading in step aerobics. Subjects participating in the research were instructors (n = 15) and students (n = 15) without any prior experience in step aerobics. Kinematic and kinetic data was collected with the use of the BTS SMART system comprised of 6 calibrated video cameras and two Kistler force plates. The subjects' task was to perform basic steps. The following variables were analyzed: vertical, anteroposterior, and mediolateral ground reaction forces; foot flexion and abduction and adduction angles; knee joint flexion angle; and trunk flexion angle in the sagittal plane. The angle of a foot adduction recorded for the instructors was significantly smaller than that of the students. The knee joint angle while stepping up was significantly higher for the instructors compared to that for the students. Our research confirmed that foot dorsal flexion and adduction performed while stepping up increased load on the ankle joint. Both small and large angles of knee flexion while stepping up and down resulted in knee joint injuries. A small trunk flexion angle in the entire cycle of step workout shut down dorsal muscles, which stopped suppressing the load put on the spine.